The Effectiveness of Group Discussion Method in Improving Student Learning Outcomes in Science Learning at MIN 7 Central Aceh - Hasanah (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to analyze the effectiveness of group discussion methods in improving the understanding of fifth grade students at MIN 7 Central Aceh regarding natural phenomena. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were 20 fifth grade students, consisting of 9 male students and 11 female students. The data for this study were obtained using test and observation techniques. Tests are used to measure student learning outcomes, while observations are used to analyze teacher and student learning activities during the learning process. The data analysis techniques used in this study are qualitative and quantitative descriptive analysis to determine the increase in learning outcomes and student involvement in group discussions. The results of the study showed that the application of group discussion methods can improve student learning outcomes. In the first cycle, only 65% ​​of students achieved scores above the KKM, while in the second cycle this figure increased to 85%. In addition, students' active participation in learning also increased from 60% in the first cycle to 80% in the second cycle. Thus, the use of group discussion methods can be used as an effective learning strategy in improving students' understanding of the concept of natural phenomena and encouraging their active involvement in the teaching and learning process.